2019
DOI: 10.1002/aoc.4837
|View full text |Cite
|
Sign up to set email alerts
|

Palladium oxide nanoparticles supported on graphene oxide: A convenient heterogeneous catalyst for reduction of various carbonyl compounds using triethylsilane

Abstract: Palladium oxide nanoparticles supported on graphene oxide ‐ triethylsilane was found to be an effective reductive system for a broad range of reduction processes, including the reduction of various carbonyl compounds such as aromatic aldehydes to their corresponding alcohols or methyl arene compounds, aromatic ketones to their respective alcohols or saturated compounds, aromatic acyl chlorides to their reduced compounds. The desired products were obtained in good to excellent yields under mild conditions. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…The UV–Vis spectrum of rGO‐NH 2 dispersion (Figure b) depicts a peak at ~260 nm, which confirms the chemical change in this material with respect to GO . The UV–Vis spectrum of PdCl 2 displays peaks at ~210, 240, 300, and 425 nm (Figure c) . The UV–Vis spectrum of PdNPs/rGO‐NH 2 nanocomposite comprises peaks at ~210 and 240 nm (Figure d).…”
Section: Resultssupporting
confidence: 52%
See 2 more Smart Citations
“…The UV–Vis spectrum of rGO‐NH 2 dispersion (Figure b) depicts a peak at ~260 nm, which confirms the chemical change in this material with respect to GO . The UV–Vis spectrum of PdCl 2 displays peaks at ~210, 240, 300, and 425 nm (Figure c) . The UV–Vis spectrum of PdNPs/rGO‐NH 2 nanocomposite comprises peaks at ~210 and 240 nm (Figure d).…”
Section: Resultssupporting
confidence: 52%
“…In continuation of our investigation in catalysis, we assessed the efficacy of PdNPs/rGO‐NH 2 nanocomposite as a heterogeneous catalyst for C–C bond formation via the Mizoroki–Heck cross‐coupling reaction of aromatic halides with alkenes. The synthesis of methyl cinnamate from the reaction of iodobenzene (0.5 mmol) with methyl acrylate (1 mmol) in the presence of PdNPs/rGO‐NH 2 nanocomposite (4 mg) was selected to optimize the coupling reaction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Out of various metal nanoparticle supports reported like MnO 2, alumina, graphene oxide and cerium oxide, silica MCM‐41 as support pertaining its high surface area (∼1000 m 2 /g)ek; and pore diameter . Being a porous material, it is capable of providing more active sites to the reactant and permitting both internal and external catalysis .…”
Section: Introductionmentioning
confidence: 99%
“…Mirza‐Aghayan et al [ 129 ] reported reduction of carbonyl compounds to corresponding methylene derivatives in the presence of Et 3 SiH using PdONPs/GO (3.6 g) as a catalyst and ethanol as a solvent system at room temperature in 10–90 min (Scheme 15). An efficient, inexpensive, and eco‐benign nature, high reusability, and recyclability are the advantages of the catalyst.…”
Section: Go‐supported Metals As Catalystmentioning
confidence: 99%